The Influence of Percieved Usefulness, Percieved Ease of Use, and Percieved Risk on the Level of Customer Satisfaction in Using Internet Banking : Study on Deposit Customers of Bank Syariah Indonesia KCP Malang Kawi - CANDRAWATI, Triesti; WIDIASTUTI, Retno (International Journal of Environmental, Sustainability, and Social Science, 2024)
The provision of services to customers in banking has experienced a very good change in connection with technological developments, where the business strategy in the banking world has placed information technology as the main factor in serving its customers. Information technology advancements have alsi sparked innovation in the service sector, including banking service. Internet banking is a form of electronic transaction which is a new form of development of bank service delivery channels which has changed a banking business strategy that initially relied more on human technology to become information technology. The aim of this research is to determine the effect of perceived usefulness perceived ease of use, and perceived risk on satisfaction with using internet banking. The population of this research is 100 priority customers at Bank Syariah Indonesia KCP Malang Kawi. While the number of samples obtained 80 priority customers using purposive sampling method. Testing the hypothesis of this study using multiple regression analysis. Conclusions that can be drawn based on the test results include the Usefulness variable, the Ease of Use variable, and the Risk variable which have a positive and significant effect, both partially and simultaneously, on the level of customer satisfaction in using Internet Banking.